The Effects of Different Energy and Protein Ratio to Sheep’s Nutrient Intake and Digestibility - Sri Mawati; S. Soedarsono; S. Sunarso; Agung Purnomoadi (Chemical Engineering Diponegoro University, 2013)
The objective of this research was to study the effects of different energy and protein ratio towards sheep’s nutrient intake and digestibility. Twenty four male sheep’s, 6 – 7 months old with initial average live weight 13+1.56 kg, coefficient variant11.78%) were used in this research. The complete feed ration which consisted of King Grass (Pennisetum purpureum), soybean powder, rice bran, dried cassava and molasses was used in this research. Protein content on each component was 10, 12 and 14% and total digestible nutrients (TDN) 60 and 65%, respectively. Dry matter (DM) and organic matter (OM) intake, DM and OM digestibility were studied in this research. Analysis of variance (ANOVA) was employed to analyze the data. Test of Small Difference (P<0.05) was then carried out if significant different occurred. The research results showed that Dry matter and OM ration intake showed significant different among treatments (P<0.05). The highest DM intake was obtained at crude protein (CP) 14% and TDN 65% i.e. 695.54 g while the lowest value was CP 14% and TDN 65% i.e. 462.11 g. Thus different DM and OM intake were caused by different ration ingredients composition. Dry matter and OM ration digestibility were not show different (P>0.05) among crude protein and TDN treatments. Different energy and protein ration treatments caused different DM and OM intake but were not cause different in DM and OM digestibility. Based on the research results, a study on the effects of different ration’s energy and protein ratio towards N efficiency should be conducted in order to increase cattle productivity. Doi: http://dx.doi.org/10.12777/ijse.4.2.75-79 [How to cite this article: Mawati, S., Soedarsono, S., Sunarso, S. & Purnomoadi, A. (2013). The Effects of Different Energy and Ratio to Sheep’s Nutrient Intake and Digestibility. International Journal of Science and Engineering, 4(2),76-79. Doi: http://dx.doi.org/10.12777/ijse.4.2.75-79]